Superdiversity and translocal brutality in Asian extreme metal lyrics. (November 2021) - Birnie-Smith, Jess; Robertson, Wesley C.
Abstract: This paper explores how local linguistic resources can transform into indexes of transnational subcultures. Drawing on indexicality and chronotopic frame theory, we examine how the lyricists of two Asian extreme metal bands selectively draw on Chinese, Taiwanese, and Japanese language features to reproduce a metal affect known as 'brutality', expanding the chronotopic configuration of forms formerly considered strictly local to communicate with a global participation framework and create complex layers of social meaning. The findings illuminate new directions for superdiversity research by questioning the presumed necessity of presupposed 'international' languages or explicit 'borrowings' in participating within a translocal scene. Highlights: Shows how local language forms can index translocal affects/identities. Illustrates how forms can be transformed to expand their chronotopic configurations. Questions presumed necessity of 'outside' forms in engaging with international scenes. Explains how participation frameworks influences variants' interpretation.